Incidence, prevalence, and disease burden of low back pain in China: data from the global burden of disease database - Zheng, Xiaodong; Han, Wenjin; Liu, Ming; Liu, Lijun; Ma, Mingtao; Ye, Zonglin; Ma, Mengqi; Yu, Longtan (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to estimate the incidence, prevalence, and disability-adjusted life years (DALYs) of low back pain (LBP) in China by gender and age based on data from the Global Burden of Disease (GBD) 2021.MethodsJoinpoint software was used to identify the turning points and significant changes (p < 0.05) in the disease burden of LBP from 1990 to 2021, and calculate the average annual percentage change (AAPC) to quantify the overall rate of trend change. The Age Period Queue (APC) model is used to explore the long-term trends and influencing factors of the burden of LBP.ResultsFrom 1990 to 2021, both incidence and prevalence rates of LBP were higher in women than in men. The incidence of LBP increased with age, and the number of affected individuals began to rise significantly starting in 1995.ConclusionIn light of the findings regarding the LBP burden in China, more efforts should be directed toward prevention and treatment for women and older adults. Furthermore, there is a need to further promote health awareness throughout the population.